Tuning the crystalline microstructure of Al-doped ZnO using direct ink writing. (21st September 2017) - Torres Arango, M A; Abidakun, O A; Korakakis, D; Sierros, K A
Abstract: ZnO-based materials are commonly used in electronic device fabrication due to the interesting piezoelectric, pyroelectric, and optical properties of this tunable band-gap semiconductor. In this research, Al-doped ZnO structures have been fabricated through continuous-flow direct writing of sol–gel inks on glass substrates. We focus on understanding the transformations occurring in the materials synthesis from solution to crystalline structures as an essential step for their use in electronic devices. We investigate the relationships between the inks' rheological properties and direct writing parameters with respect to the printed pattern dimensions, and obtained microstructures, after annealing at 500 °C. We demonstrate how, by varying the printing conditions and composition of the ink formulations, the crystallographic-growth and materials' microstructure can be controlled. Finally, we illustrate an example of the optoelectronic functionality of the directly written AZO patterns using their photosensitivity properties upon different illumination conditions as well as their flexibility. Our work aims to establish relationships between materials processing and properties in emerging additive printing methods, which is of paramount importance towards innovation and new paradigms in advanced manufacturing.